AGAMA DAN PERUBAHAN SOSIAL (Modernisasi Pendidikan Di Dunia Islam) - ZAINUDDIN HAMKAH (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
Modernization in Western society implies thoughts, currents, movements and efforts to change old understandings, customs, institutions and so on, to suit the new atmosphere brought about by advances in modern science and technology. The advancement of modern science and technology entered the Islamic world, especially after the opening of the 19th century AD which in Islamic history is seen as the beginning of the modern period. Contact nationalism, nationalism, democracy and so on. All this gave rise to new problems and the Islamic leaders began to think about how to solve the new problems. As is the case in the West in the Muslim world, ideas and movements have also arisen to adapt Islamic religious ideas to new developments brought about by advances in modern science and technology. In this way, modern Islamic leaders hope to release Muslims from an atmosphere of decline to be brought to progress. Renewal can be carried out without leaving religion. What needs to be left in the renewal is a tradition that is contrary to the times.